Extreme Learning Machine for Biomedical Image Classification: A Multi-Case Study - Mercaldo, Francesco; Brunese, Luca; Santone, Antonella; Martinelli, Fabio; Cesarelli, Mario (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
In the current realm of biomedical image classification, the predominant choice remains deep learning networks, particularly convolutional neural network (CNN) models. However, deep learning suffers from a notable drawback in terms of its high training cost, mainly due to intricate data models. A recent alternative, known as the Extreme Learning Machine (ELM), has emerged as a promising solution. Empirical investigations have indicated that ELM can offer satisfactory predictive performance for a wide array of classification tasks, while significantly reducing training costs when compared to deep learning networks trained using back propagation.This research paper introduces a methodology designed to evaluate the suitability of employing the Extreme Learning Machine for biomedical classification tasks. Our study encompasses binary and multiclass classification across four distinct scenarios, involving the analysis of biomedical images obtained from both dermatoscopes and blood cell microscopes. The findings underscore the effectiveness of the Extreme Learning Machine, showcasing its successful utilization in the classification of biomedical images.
Keywords: Extreme Learning Machine; ELM; Biomedical Image; Classification; Machine Learning